Pengaruh Motivasi Kerja Dan Disiplin Kerja Terhadap Kepuasan Kerja Di J&T Cabang Tasikmalaya Kecamatan Bungursari - Rendi Muhamad Prayoga; Rita Tri Yusnita; Ai Kusmiati Aisyah (Dinamika Publik: Jurnal Manajemen dan Administrasi Bisnis, 2023)
This study aims to determine the Effect of Work Motivation and Work Discipline on Job Satisfaction of employees of J&T Tasikmalaya. This study uses a causality and survey quantitative method. The type of data used is primary data and secondary data, with a sample of 40 respondents from the employees of J&T Tasikmalaya, and using the saturated sample method. The data analysis tool used in this study was SPSS V.25. Data collection techniques used interviews, questionnaires, and literature studies. The results of the study show that the Work Motivation and Work Discipline have a significant effect on Job Satisfaction. Work Motivation partially have a significant effect on Job Satisfaction. Work Discipline partially has a significant effect on Job Satisfaction.